Roles of community towards urban farming activities - Mohd Yusoff, Norul Hafizah; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati (MIP Planning Malaysia, 2017)
The aim of this paper is to review and analyse the importance of the framework for urban farming activities to be implemented within cities environment. This paper also describes the role of the community to achieve the environmental,economic and social sustainability for the enhancement of the urban environment and healthy lifestyles through community participation in food supplies, nutrition, and spaces utilization. The paper evaluates the benefits and potential of urban farming activities within limited urban spaces and how it improves the quality of life. It also reviews on how urban farming is beneficial to the society due to food shortage crisis which is inadequate for the whole population. It is necessary to apply and practice in our daily lives for the consumption of food security, human safety, and health. Therefore, the role of community is very crucial in the implementation of urban farming activities within urbanized areas as the demand for green development increases. Based on this theoretical framework, it is hoped that the paper will be a useful addition to the body of knowledge in promoting a stronger community interdependence to create the sustainable urban environment.